2022
DOI: 10.1155/2022/6235747
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Is a Vital Driving Force in Ischemia-Reperfusion Injury in Cardiovascular Diseases

Abstract: According to the latest Global Burden of Disease Study, cardiovascular disease (CVD) is the leading cause of death, and ischemic heart disease and stroke are the cause of death in approximately half of CVD patients. In CVD, mitochondrial dysfunction following ischemia-reperfusion (I/R) injury results in heart failure. The proper functioning of oxidative phosphorylation (OXPHOS) and the mitochondrial life cycle in cardiac mitochondria are closely related to mitochondrial DNA (mtDNA). Following myocardial I/R in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 211 publications
(227 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, this research demonstrated that HJ11 decoction could mitigate the apoptosis of cardiomyocytes in the myocardial I/R injury rat model. CK-MB and LDH are sensitive factors for the evaluation of myocardial I/R injury ( Liu et al, 2022 ). Aberrant expression of CK-MB and LDH can suppress the antioxidant potential of cardiomyocytes ( Liu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this research demonstrated that HJ11 decoction could mitigate the apoptosis of cardiomyocytes in the myocardial I/R injury rat model. CK-MB and LDH are sensitive factors for the evaluation of myocardial I/R injury ( Liu et al, 2022 ). Aberrant expression of CK-MB and LDH can suppress the antioxidant potential of cardiomyocytes ( Liu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the accumulation of 8-oxoG in mtDNA, rather than in nuclear DNA, may be involved in renal tubular cell injury and other pathological reactions caused by renal ischemia-reperfusion injury. In cardiac ischemia-reperfusion injury model studies, mtDNA damage repaired by OGG1 base excision seemed to have no significant effect on cardiac function [123,124]. In an ischemia-reperfusion model, the DNA repair function of OGG1 is inhibited under oxidative stress, and the upregulated OGG1 levels may also have other transcriptional regulatory effects, which require further study.…”
Section: Ogg1 In Akimentioning
confidence: 98%
“…Mitochondria are the only organelle possessing their circular genome, which is 16.6 kb in mammals, encoding 13 subunits that are essential in the maintenance and regulation of mitochondrial functions, such as encoding essential proteins of ETC and OXPHOS system ( Liu H. et al, 2022 ). As mtDNA exists within the mitochondrial matrix or attached to the IMM, it can be easily damaged by free radicals produced by the respiratory chain.…”
Section: Ci/ri and Mitochondrial Dysfunctionsmentioning
confidence: 99%